(untitled) (Global Journal of Science Frontier Research, 2024)
Life of a living being is mathematically modelled as a Quartic Power Curve in the time Then we compute the Energy of Life of such an individual as a Quintic in the time More applications of this model to real life will follow in the future now just the basic mathematics is described in this brand-new paper